Microfinance and Poverty Alleviation in Burundi: Assessing the Role of Financial Inclusion in Sustainable Development Goals (SDGs) - Jean-Baptiste Innocent Nyangoma, Jean-Baptiste Innocent Nyangoma; Amina Njeri Kamau; Rakesh Kumar Sharma (Journal GoodWill, 2024)
This study investigates the role of financial inclusion in enhancing the effectiveness of microfinance programs in reducing poverty in Burundi, with a particular focus on their contribution to the Sustainable Development Goals (SDGs), especially SDG 1 (No Poverty) and SDG 8 (Decent Work and Economic Growth). Employing a mixed-method research design, the study collected data from 420 microfinance beneficiaries across four provinces through surveys and semi-structured interviews. Using multiple regression and structural equation modeling (SEM), the findings reveal that financial inclusion significantly mediates the relationship between microfinance participation and household welfare improvement. Access to financial services—such as savings, credit, and mobile banking—positively influences income generation, consumption stability, and business expansion among low-income households. However, the study also identifies barriers including high interest rates, limited outreach in rural areas, and low levels of financial literacy, which constrain the inclusiveness of microfinance initiatives. The results suggest that microfinance alone is insufficient to achieve sustainable poverty alleviation without complementary strategies such as financial literacy enhancement, gender-sensitive credit policies, and digital financial innovation. The study concludes that strengthening financial inclusion is essential for transforming microfinance into an effective instrument for inclusive and sustainable development in Burundi.